The quest for identity through a Rorschach protocol in the adolescent who marks his skin: presentation of a case. - DEHANE , Amel (Journal of Human Sciences, 2022)
Body markings are ancestral practices, which come back in an individual approach. Algeria is no exception to this phenomenon and is experiencing a renewed interest in young adolescents for these ancient and traditional practices. Our interest is based on clinical observations supported by an exploratory survey of 200 young people. From there, the psychic processes underlying body marking will be examined in 10 adolescents, based on research interviews and projective tests (RORSCHACH and TAT). In this paper, we will limit ourselves to presenting a case, that of Mohamed, and trying to know the elements and clues we allow to distinguish the defense mechanisms, the nature of anxiety and the object relationship through the Rorschach.